1996
DOI: 10.1111/j.1476-5381.1996.tb15471.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanisms involved in adenosine‐5′‐O‐(2‐thiodiphosphate) induced relaxation of rat thoracic aorta and pancreatic vascular bed

Abstract: 1 The endothelium-dependent relaxation of blood vessels induced by P2y-purinoceptor activation has often been shown to involve prostacyclin and/or nitric oxide (NO) release. In this work, we have investigated the mechanisms involved in the relaxant effect of the P2y agonist, adenosine -5'-O-(2-thiodiphosphate) (ADPflS) using two complementary preparations: rat pancreatic vascular bed and aortic ring.2 On the pancreatic vascular bed, ADPPS (1.5 and 15 gM) infused for 30 min induced a concentrationdependent vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…Endothelium-dependent relaxation by ATP and other nucleotides has also been demonstrated in the rat aorta (Rapoport et al 1984;White et al 1985;Rose'Meyer and Hope 1990;Dainty et al 1991Dainty et al , 1994Dominiczak et al 1991;Frew et al 1993;Mombouli and Vanhoutte 1993;García-Velasco et al 1995;Saïag et al 1996). The rank order of agonist potency MeSATP > UTP = ATP García-Velasco et al 1995) is consistent with a mixed P2Y and P2U population .…”
Section: Introductionmentioning
confidence: 52%
“…Endothelium-dependent relaxation by ATP and other nucleotides has also been demonstrated in the rat aorta (Rapoport et al 1984;White et al 1985;Rose'Meyer and Hope 1990;Dainty et al 1991Dainty et al , 1994Dominiczak et al 1991;Frew et al 1993;Mombouli and Vanhoutte 1993;García-Velasco et al 1995;Saïag et al 1996). The rank order of agonist potency MeSATP > UTP = ATP García-Velasco et al 1995) is consistent with a mixed P2Y and P2U population .…”
Section: Introductionmentioning
confidence: 52%
“…Adenosine-59-(b-thio)-diphosphate, a P2Y 1 -selective agonist, caused endothelium-dependent vasodilatation of the rat isolated perfused pancreas, which was mediated partly by NO and PGI 2 but also through another mechanism that did not involve K ATP , SK Ca , and BK Ca channels (Saïag et al, 1996;HillaireBuys et al, 1998). P2X 1 , P2X 2 , P2Y 1 , and P2Y 2 receptor expression was shown using immunohistochemistry in small blood vessels of the rat pancreas (Coutinho- Silva et al, 2003).…”
Section: R Other Blood Vesselsmentioning
confidence: 99%
“…Similarly, in rat mesenteric arteries, it has been reported that stimulation of the P 2Y receptors triggers endothelium-dependent relaxation, which was inhibited by the combination of iberiotoxin and apamin in the presence of L-NOARG and indomethacin [9]. Recent studies also suggests that activation of the P 2Y receptors induces endothelium-dependent vasodilation mediated by EDHF [10,11,14,15,18]. Therefore, it is suggested that ADP β S activates the P 2Y receptors to release EDHF from endothelial cells of the rabbit renal arteries.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies suggest that activation of the P 2Y receptors induces endothelium-dependent vasodilation mediated by EDHF [10,14,15,18]. In the rat mesenteric artery, P 2Y receptor-induced vasodilatation is antagonized by a combination of the K + channels inhibitors, charybdotoxin and apamin, which prevents hyperpolarization and relaxation mediated by EDHF in different blood vessels [3,9,20].…”
mentioning
confidence: 99%